Endoscopic Submucosal Dissection of Deeply Invasive Colorectal Cancers Using the Pocket-Creation Method: Analysis of Vertical Margins - Morikawa, Takaaki; Hayashi, Yoshikazu; Fukuda, Hisashi; Ishii, Hiroaki; Nomura, Tatsuma; Ikeda, Eriko; Kitamura, Masafumi; Kagaya, Yuka; Okada, Masahiro; Takezawa, Takahito; Sunada, Keijiro; Lefor, Alan Kawarai; et al. (Frontiers in Gastroenterology, 2022)
Background and aims: The standard treatment for stage T1b colorectal cancers with 1,000µm or greater submucosal invasion is surgical resection. However, the risk of lymph node metastases is only 1-2% when excluding risk factors for metastases other than depth of submucosal invasion. The number of elderly patients with significant comorbidities is increasing with societal aging in Japan. Therefore, local endoscopic resection of T1b colorectal cancers needs more consideration in the future. We previously showed that the pocket-creation method (PCM) for endoscopic submucosal dissection (ESD) is useful regardless of the morphology, including large sessile tumors with submucosal fibrosis, or location of the colorectal tumor. However, some T1b colorectal cancers have pathologically positive margins even when using the PCM. We retrospectively investigated the causes of failure to achieve negative vertical margins. Methods: We retrospectively analyzed 953 colorectal tumors in 886 patients resected with the PCM. Finally, 65 pathological T1b colorectal cancers after en bloc resection were included in this study. ESD specimens and recorded procedure videos of T1b cancer resections with pathologically positive vertical margins were reviewed. Results: The 65 cancers were divided into positive vertical margin (VM+ group) and negative vertical margin (VM- group) groups with 10 (10/65 [15%]) and 55 (55/65 [85%]) patients in each group, respectively. There was a significant difference in the rate of submucosal fibrosis (P=0.012) and dissection speed (P=0.044). There were no significant differences between the two groups in other regards. When verifying 8/10 available videos in the VM+ group, endoscopic technical factors led to positive vertical margins in five patients, and essential pathological factors of ESD led to positive vertical margins in the other three. Six of these eight patients underwent additional surgical resection. No residual tumor was identified in six T1b cancers. None of these six resected specimens contained lymph node metastases on pathological examination. Conclusion: The PCM resulted in a high rate of negative-vertical-margin resections. The PCM resulted in complete resection of T1b cancers when examining additional surgical specimens. ESD using the PCM is a viable option for the endoscopic treatment of T1b colorectal cancers.